Development of an Integrated Web Portal for Universities, Faculties, and Study Programs - Muhammad Hakim; Anggi Andika Pratama; Arga Chon Feriandref; Othman Ballan; Riman Abimayu; Beni Liantori; Irfan Widyanto; Sahril Saputra (JSI: Jurnal Sistem Informasi (E-Journal), 2026)
Digital transformation in the university environment requires the availability of an integrated, adaptive, and easily accessible information system for all academics. Universitas Graha Karya Muara Bulian (UGKMB) implements an integrated web portal that includes university, faculty, and study program portals as the main means of delivering academic and non-academic information. This study aims to analyze the implementation of the UGKMB portal consisting of the university portal (https://ugkmb.ac.id), the portal of the Faculty of Agriculture, Science and Technology (http://fpst.ugkmb.ac.id/), and the portal of the Information Systems Study Program (http://si.ugkmb.ac.id/). The research method used is a qualitative descriptive method with a case study approach, including needs analysis, system design, implementation, and functional evaluation. The results of the study show that the implementation of an integrated portal is able to improve information consistency, content management efficiency, and accessibility of academic information services. The integration of web structures and identities between organizational levels also supports strengthening institutional branding and information transparency. This research is expected to be a reference for other universities in developing structured and sustainable academic web portals.